School Attendance Pre and Post Home Infusion Therapy - Hummel, L. (Thrombosis and Haemostasis, 1977)
To compare the relationship between home infusion therapy and school attendance, 21 official school records of hemophilic boys on home infusion therapy were analyzed. The records show a mean absence of 40.4 days for one year pre and 25.3 days post home infusion therapy. Data included 18 subjects with two year pre and post home infusion therapy records. These 18 subjects had a mean absence of 40.9 days for two years pre and 26.4 days for two years post home infusion therapy. Data indicate boys on home infusion therapy have better school attendance than they did before home infusion therapy. The length of time they were on home infusion therapy did not seem to be significant. The grades in which the children were studied was also not significant.